(untitled) - Tanjutek (Singapore, 1998)
This book introduce about the new perspective, the curse, basic human needs, the deadly obsession, evil race carnage and legacy, the global invasion, profile and tactics of the evil race, international dictatorship and terrorism, evil race racism...
Keywords: Lịch sử thế giới,World history